Blasphemy Laws and Their Implications for Religious Freedom and Expression: A Tri-Country Southeast Asian Perspective - Situmeang, Ampuan; Rusdiana, Shelvi; Trinh, Hien; Agustianto, Agustianto; Tan, Winsherly (Jurnal Hukum, 2024)
Blasphemy laws, while deemed important by some in protecting religious beliefs and practices, can have implication of conflicts with human rights. Utilizing comparative legal research method, this research aims to analyze how blasphemy laws in Indonesia and Thailand affect freedom of expression and religion. Findings of this study highlight the interplay between blasphemy laws, freedom of expression, and freedom of religion. This study also highlights the existing legal norms within relevant positive laws in Indonesia, Thailand, and Vietnam, that have implication of conflicts with freedom of expression and freedom of religion. Indonesia presents the most complex conflict between these human rights, while Thailand, despite offering greater freedom of expression, normatively falls short in religious freedom due to its preferential treatment of Buddhism and its clergy. Vietnam has the least implication of conflicts, as it only governs the prohibition against profaning a religion, which is significantly different than what constitutes as blasphemy, and allowing little to no room for multi interpretation.